IMPLEMENTATION OF HIWALAH AGREEMENT AGAINST TAKERS – TRANSFER OF SUBSIDIZED FERTILIZER DEBT AT PUSRI RETAILERS KPL. SURYA USAHA TANI - Fatchurrohman, M; Syihabudin, Ahmad (AL HUKMU: Journal of Islamic Law and Economics, 2023)
Hiwalah is the transfer of the right to claim debts to other (third) parties on the basis of the consent of the party who gives the debt. The basis of the hiwalah contract is that ta'awun is a help- helping activity in the good among fellow Muslims. Reseller Pusri KPL. Surya Usaha Tani sells fertilizer with a tempo system with a gradual payment after the rice harvest, the results of which cannot be ascertained. The debt of the fertilizer slasher in Pusri is paid by farmers after getting money from the sale of their paddy harvest. However, in the payment, there is an additional cost of fertilizing rice fields for which there is no record of costs as a statement. The additional payments are not clearly known to farmers which is a common occurrence in the local community. However, in Islamic law the transaction of Hiwalah with Ujroh must have special records and particulars so that it can be proved and known together and not become gharar (Unclear). Implementation of hiwalah agreements for takers – transfer of subsidized fertilizer debt at pusri retailers KPL. Surya Usaha Tani needs research to be able to positively influence the surrounding community who do not understand hiwalah transactions clearly. It is also in the case of unilateral pricing of retailers and the system of expropriating fertilizer debts with the lack of clarity on the exact costs to these farmers needs to be analyzed under Islamic law against the Subsidized Fertilizer Debt Takers. The research method used in this study uses qualitative methods with the type of library research and also uses field research. Primary data sources are obtained from interviews with respondents while secondary data sources are obtained through books, literature studies, and various other sources. The data collection techniques used are observation, interview and documentation directly. The results of the analysis showed that the practice of transferring the debt of the farmers with KPL. Surya Usaha Tani told The Rice Slasher that there was no agreement at the beginning on all additional services in finding workers who were willing to work on seeding fertilizer and also transportation services in the transportation of fertilizer which was measured from the distance traveled and the constraints of transporting fertilizer to several different rice fields. Then Hiwalah was shari'a by Islam and allowed because there was a maslahat to help and facilitate in muamalah activities because it included evidence of mutual help to others. Hiwalah KPL. Surya Usaha Tani is allowed under Islam if in the implementation of the hiwalah contract which coincides with wages (ujroh) on the transfer of farmers' debts by KPL. Surya Usaha Tani to the rice slasher has a clearly written agreement along with the witness so that in the agreement in cutting the crop for fertilizer debt and other costs so that both parties feel willing in the existence of the transaction.